2016
DOI: 10.14301/llcs.v7i1.360
|View full text |Cite
|
Sign up to set email alerts
|

The Swiss Household Panel Study: Observing social change since 1999

Abstract: Collecting data on households and individuals since 1999, the Swiss Household Panel (SHP) is an ongoing, unique, large--scale, nationally representative, longitudinal study in Switzerland (N=7,383 households and N=12,119 persons interviewed in 2014). The data of the SHP provide a rich source of information to study social change in Switzerland over a significant period on a wide variety of topics. The SHP aims to provide both continuity and innovation in measurement and data collection, with the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 20 publications
0
52
0
Order By: Relevance
“…We used the data from all three SHP samples, i.e., from the original SHP I sample drawn in 1999, the SHP II refreshment sample drawn in 2004, and the SHP III refreshment sample drawn in 2013. The initial wave response rate at the household level was 64% (SHP I), 65% (SHP II), and 60% (SHP III), and at the individual level conditional on household participation was 85% (SHP I), 76% (SHP II), and 81% (SHP III) (Tillmann et al 2016). The re-interview rate at the household level was between 78% (SHP II in 2006) and 94% (SHP I in 2010, 2013, and 2015 3 ).…”
Section: Data and Samplementioning
confidence: 98%
See 1 more Smart Citation
“…We used the data from all three SHP samples, i.e., from the original SHP I sample drawn in 1999, the SHP II refreshment sample drawn in 2004, and the SHP III refreshment sample drawn in 2013. The initial wave response rate at the household level was 64% (SHP I), 65% (SHP II), and 60% (SHP III), and at the individual level conditional on household participation was 85% (SHP I), 76% (SHP II), and 81% (SHP III) (Tillmann et al 2016). The re-interview rate at the household level was between 78% (SHP II in 2006) and 94% (SHP I in 2010, 2013, and 2015 3 ).…”
Section: Data and Samplementioning
confidence: 98%
“…We use data from the Swiss Household Panel (SHP), which has been surveyed annually since 1999 (Tillmann et al 2016). As a nationally representative longitudinal data set that simultaneously measures life satisfaction, family structure, employment situation, and job insecurity, the SHP is well suited to address the questions raised in this study.…”
Section: Data and Samplementioning
confidence: 99%
“…In total, 28,101 individuals have ever responded to the individual questionnaire. Details on the study design, response and attrition can be found in Tillmann et al (2016).…”
Section: Datamentioning
confidence: 99%
“…The different subsamples of SHP (Tillmann et al 2016) participants who completed the individual questionnaire are defined differently depending on the transition under study. For each transition, individuals were followed from wave 3 (2001) until wave 16 (2014).…”
Section: Datamentioning
confidence: 99%